The pragmatics of political discourse : explorations across cultures - Fetzer, Anita, 1958- (Pragmatics & beyond, 2013)
"The volume promotes a pragmatic perspective to the analysis of political discourse as multilayered mediated discourse. The chapters cross the disciplinary and methodological boundaries of speech act theory, social positioning theory, and argumentation theory and rhetorics. They address the strategic use of address terms and irony, the form and function of questions, and the expression of certainty in the contexts of parliamentary discourse, interview, talkshow, phone-in programme and motion of support across different discourse domains. Different cultural contexts are represented, including Africa, the Middle East, different parts of Europe and the United States."--Provided by publisher